Application “halal path” with learning features, assistance for MSMEs in halal certification process with the use of IoT systems - Adlyn, Nathania; Waworuntu, Charlotte Corinthians; Suryawati, Rindah Febriana (Halal Studies and Society, 2024)
Muslim population in Indonesia is approximately 229.62 million, accounting for 87.2% of the country’s total population. With this large Muslim demographic, there is a growing need for Halal-certified food sources that are safe for consumption. However, many MSMEs (Micro, Small, and Medium Enterprises) in the country face significant challenges in obtaining Halal certification due to various factors. These include geographical barriers, expensive certification processes, limited understanding of online services, and public perceptions that Halal certification is unnecessary for MSMEs. To address the challenges, changes have been made to Indonesian Halal Certification System, particularly the introduction of regular and self declare programs. Therefore, this study aims to develop Halal Path application to support the self declare program for eligible MSMEs and enhance the economy, reputation, and cultural globalization of Indonesia. This initiative seeks to create safe and comfortable conditions for Muslims and improve food safety and quality. The study procedures were carried out using an academic literature review focusing on legal frameworks and Halal certification processes, which integrate Internet of Things (IoT) to streamline Halal supply chain management in industrial and agricultural contexts. The proposed Halal Path comprised 6 stages, namely educational videos on Halal system in Indonesia, video tutorials for obtaining business identification numbers (NIB), instructions for applying for Halal certification under both regular and self declare programs, Halal Assurance System (HAS) training, internal audits, and monitoring. In addition, the application “Halal Path” included a supplier information feature using IoT to help MSMEs obtain safe and Halal raw materials effectively.